Effect of Enzymatically Extracted Fucoidans on Angiogenesis and Osteogenesis in Primary Cell Culture Systems Mimicking Bone Tissue Environment - Julia Ohmes; Yuejun Xiao; Fanlu Wang; Maria Dalgaard Mikkelsen; Thuan Thi Nguyen; Harald Schmidt; Andreas Seekamp; Anne S. Meyer; Sabine Fuchs (Marine Drugs, 2020)
Angiogenesis, the formation of new blood vessels from existing ones, is an essential process for successful bone regeneration. Further, angiogenesis is a key factor for the development of bone-related disorders like osteosarcoma or arthritis. Fucoidans, sulfated polysaccharides from brown algae, have been shown to affect angiogenesis as well as a series of other physiological processes including inflammation or infection. However, the chemical properties of fucoidan which define the biological activity vary tremendously, making a prediction of the bioactivity or the corresponding therapeutic effect difficult. In this study, we compare the effect of four chemically characterized high molecular weight fucoidan extracts from Fucus distichus subsp. evanescens (FE_crude and fractions F1, F2, F3) on angiogenic and osteogenic processes in bone-related primary mono- and co-culture cell systems. By determining the gene expression and protein levels of the regulatory molecules vascular endothelial growth factor (VEGF), angiopoietin-1 (ANG-1), ANG-2 and stromal-derived factor 1 (SDF-1), we show that the extracted fucoidans negatively influence angiogenic and osteogenic processes in both the mono- and co-culture systems. We demonstrate that purer fucoidan extracts with a high fucose and sulfate content show stronger effects on these processes. Immunocytochemistry of the co-culture system revealed that treatment with FE_F3, containing the highest fucose and sulfate content, impaired the formation of angiogenic tube-like structures, indicating the anti-angiogenic properties of the tested fucoidans. This study highlights how chemical properties of fucoidan influence its bioactivity in a bone-related context and discusses how the observed phenotypes can be explained on a molecular level—knowledge that is indispensable for future therapies based on fucoidans.